APLIKASI SINGLE LINE PLN RAYON TEGOWANU MENGGUNAKANMETODE LOCATION BASED SERVICE (LBS) BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract:Single Line PLN is a diagram that described the whole electrical grid in a PLN area. This application (or  also  called:  Single  Line  Application)  aims  to  show Single Line diagram in the forms of Google Maps, that is able  to  know  and  show  the  user’s  position  within  the power  pole  location,  and  also  give  service  information from  the  user’s  location  to  the  target  location.  This application  also  provides  service  phone  numbers  that  is available  to  be  accessed  straight  away  from  user’s handphone, especially for PLN disruption officer that can use to give information to the office of PLN Tegowanu. Single Line application is madeusing IDE Eclipse with  the  project  named  project  SingleLine  dan  package com.SingleLine.  For  the  layout  design,  it  consists  of  10 XML  files,  whereas  the  listing  program  consists  of  13 Java  files.  The  storage  data  of  this  Single  Line Application  uses  SQLiteDatabase  named  SingleLine.db file and Power Pole Table file. For showing the maps, it needs Google Maps API Key which is available in Google Developers Console as an access for the map to be shown in this Single Line application. This Single Line application is mobile application based on Location Based Service (LBS) technology that is built on Android platfrom with the use of Java, XMLand SQL programming languages.Keywords: Single Line PLN, Android, Location Based Services, Google Maps